Forkhead box M1 recruits FoxP3+ Treg cells to induce immune escape in hilar cholangiocarcinoma - Kai Ma; Zhaowei Sun; Xueliang Li; Jingyun Guo; Qinlei Wang; Mujian Teng (Immunity, Inflammation and Disease, 2022)
Abstract Objective Hilar cholangiocarcinoma (HCCA) is a malignancy related to chronic biliary tract inflammation. Tumor immune escape is a necessary process of tumorigenesis. Forkhead box M1 (FoxM1) could affect the progression of various carcinomas. This study attempted to elaborate on the mechanism of FoxM1 in HCCA immune escape. Methods HCCA cell lines were collected to measure the expression of FoxM1 and FoxP3. CD8+ T cells were extracted to establish the co‐culture system with HCCA cells and Treg cells. pcDNA3.1‐FoxM1 or si‐FoxP3 was transfected into HCCA cells in the co‐culture system. HCCA cell viability, mobility, and invasiveness as well as levels of transforming growth factor (TGF)‐β and interleukin (IL)‐6 were evaluated. The binding relation between FoxM1 and FoxP3 promoter was verified. HCCA cells with pcDNA3.1‐FoxM1 were subcutaneously injected into mice to establish the xenograft mouse models. Results FoxM1 and FoxP3 were overexpressed in HCCA cells. The co‐culture of CD8+ T and HCCA cells inhibited HCCA cell activity and Treg cells limited CD8+ T killing. FoxM1 overexpression strengthened the inhibiting role of Treg cells in CD8+ T killing, upregulated TGF‐β and IL‐6 levels, and encouraged HCCA immune escape. FoxM1 bound to the FoxP3 promoter region to promote FoxP3 transcription. Silencing of FoxP3 neutralized the promoting role of FoxM1 overexpression in Treg cell immunosuppression and HCCA cell immune escape. FoxM1 aggravated tumor development, upregulated FoxP3 expression, increased Treg cells, and reduced CD8+ T cells. Conclusion FoxM1 bound to the FoxP3 promoter region to promote FoxP3 transcription and recruited FoxP3+ Treg cells, thereby inducing HCCA immune escape.